Characterization of sick leave by military police officers in Belém of Pará (Research, Society and Development, 2020)
The activity of the military police has several mechanisms that reduce the quality of life of these professionals, for which the numbers of sick leave for health reasons are increasingly more expressive, especially in the metropolitan region of Belém. Thus, the objective is to characterize the types of musculoskeletal injuries that occur in Military Police officers in exercise from the classification of the Medical Board of the Military Police of the State of Pará. This was a documentary research, in a time frame from 2012 to 2018, with a quantitative approach. Among the main results, it is highlighted that 63.48% of the police officers who requested leave reported only one type of disease, the maximum time away was a little over 10 years and the minimum time was 6 days. The year 2012 presented the highest number of requests (35113), while the last year of the investigated period registered an important decrease in requests (14436). These data corroborate the need for further investigation of the theme, linked to factors that may promote the prevention of the appearance of musculoskeletal injuries, given that many are the factors that contribute to the development of physical and mental health problems, where numbers are observed expressive absences for the treatment of various diseases, this study sought to emphasize pathologies of orthopedic origin.